(untitled) (Medical Forum Monthly, 2024)
Objective: The purpose of this study is comparison of patient satisfaction and functional treatment outcomes of parasymphysis fractures treated with two mini-plates and one mini-plate along with arch bar. Study Design: Prospective Comparative study Place and Duration of Study: This study was conducted at the Department of Oral & Maxillofacial Surgery, Sardar Begum Dental College and Hospital, Peshawar and Northwest General Hospital Peshawar from July to Dec. 2018. Materials and Methods: 60 patients with diagnosed isolated parasymphysis fracture were included in the study. Two mini-plates were used for treatment in 30 patients in Group (A), while 30 patients in Group (B) were treated with one mini-plate with arch bar. The operative time and cost of the treatment was noted from start till end. Patient were checked at 15 days & 1 ,3 and 6-months follow up visits for effect on the quality of life by measuring the number of days missed from work, return to normal diet and duration of bed rest and was comparison was made between both the groups. Results: The mean operating time in group A was 61.49 minutes while in group it was 47.93 minutes. The average cost of treatment in group A was 8533.33 rupees while in group B it was 4383.33 rupees. The effect on quality of life was more for patients with group B than A. Conclusion: Patients treated with two miniplates have higher cost and greater operating than patients treated with one miniplate along arch bar but have improved quality of life than arch bar group